Genome-Wide Identification of Effector Candidates With Conserved Motifs From the Wheat Leaf Rust Fungus Puccinia triticina - Zhao, Shuqing; Shang, Xiaofeng; Bi, Weishuai; Yu, Xiumei; Liu, Daqun; Kang, Zhensheng; Wang, Xiaojie; Wang, Xiaodong (Frontiers in Microbiology, 2020)
Rust fungi secrete various specialized effectors into host cells to manipulate the plant defense response. Conserved motifs, including RXLR, LFLAK-HVLVxxP (CRN), Y/F/WxC, CFEM, LysM, EAR, [SG]-P-C-[KR]-P, DPBB_1 (PNPi), and ToxA, have been identified in various oomycete and fungal effectors and are reported to be crucial for effector translocation or function. However, little is known about potential effectors containing any of these conserved motifs in the wheat leaf rust fungus (Puccinia triticina, Pt). In this study, sequencing was performed on RNA samples collected from the germ tubes (GT) of uredospores of an epidemic Pt pathotype PHTT(P) and Pt-infected leaves of a susceptible wheat cultivar “Chinese Spring” at 4, 6, and 8 days post-inoculation (dpi). The assembled transcriptome data were compared to the reference genome of “Pt 1-1 BBBD Race 1”. A total of 17,976 genes, including 2,284 “novel” transcripts, were annotated. Among all these genes, we identified 3,149 upregulated genes upon Pt infection at all time points compared to GT, whereas 1,613 genes were more highly expressed in GT. A total of 464 secreted proteins were encoded by those upregulated genes, with 79 of them also predicted as possible effectors by EffectorP. Using hmmsearch and Regex, we identified 719 RXLR-like, 19 PNPi-like, 19 CRN-like, 138 Y/F/WxC, and 9 CFEM effector candidates from the deduced protein database including data based on the “Pt 1-1 BBBD Race 1” genome and the transcriptome data collected here. Four of the PNPi-like effector candidates with DPBB_1 conserved domain showed physical interactions with wheat NPR1 protein in yeast two-hybrid assay. Nine Y/F/WxC and seven CFEM effector candidates were transiently expressed in Nicotiana benthamiana. None of these effector candidates showed induction or suppression of cell death triggered by BAX protein, but the expression of one CFEM effector candidate, PTTG_08198, accelerated the progress of cell death and promoted the accumulation of reactive oxygen species (ROS). In conclusion, we profiled genes associated with the infection process of the Pt pathotype PHTT(P). The identified effector candidates with conserved motifs will help guide the investigation of virulent mechanisms of leaf rust fungus.